Chloro Derivatives of Azafullerenes C59NCl5 and Non‐Classical C97NCl21. Issue 3 (6th January 2017) - Markov, Vitaliy Yu.; Troyanov, Sergey I.
Abstract: High‐temperature chlorination of HPLC fullerene fractions containing mainly C92 /C94 and C102 /C104 resulted in the isolation and X‐ray structural characterization of chloro derivatives of azafullerenes, C59 NCl5 and C97 NCl21 . It was assumed that formation of azafullerenes in the arc‐discharge synthesis of fullerenes occurred due to air leakage into the reactor. The molecule of C59 NCl5 contains an isolated aromatic pyrrole ring on the fullerene cage and possesses C 5 v symmetrical shape typical of other known C59 NR5 derivatives. The molecule of non‐classical ( NC ) C97 N( NC )Cl21 contains an NC6 heptagon on the azafullerene cage that assumes its formation by a C2 loss from C99 N in the course of chlorination. The chlorination pattern is characterized by the presence of stabilizing isolated aromatic systems and isolated double C=C bonds on the C97 N( NC ) azafullerene cage. Abstract : Unexpected C/N replacement : An X‐ray crystallographic study of chloro azafullerenes revealed the structures of C59 NCl5 and non‐classical C97 N( NC )Cl21 . The C59 NCl5 molecule contains an isolated aromatic pyrrole ring on the fullerene cage and possesses a C 5 v symmetrical shape (see picture). The C97 N( NC )Cl21 molecule contains an NC6 heptagon on the fullerene cage that assumes its formation by a C2 loss from aza[100]fullerene in the course of chlorination. Most probably, the formation of azafullerenes in the arc‐discharge fullerene synthesis occurred due to air leakage into the reactor.